2017
DOI: 10.1038/cmi.2017.16
|View full text |Cite|
|
Sign up to set email alerts
|

A crucial role of the PD-1H coinhibitory receptor in suppressing experimental asthma

Abstract: Programmed death one homolog (PD-1H) is a cell surface molecule of the B7/CD28 immune modulatory gene family. Although PD-1H has been shown to function as a coinhibitory receptor on T cells to limit naive T-cell activation and proliferation, its role in the regulation of the T-cell response to allergens is unknown. We report here that genetic ablation or blockade of PD-1H drastically promotes pulmonary inflammation with massive accumulation of eosinophils in a mouse model of experimental asthma, indicating a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 22 publications
5
40
1
Order By: Relevance
“…Similar results were recently reported in the Fas lpr lupus model where VISTA‐deficiency enhanced disease while VISTA agonists suppressed both cutaneous and systemic lupus . In addition, VISTA‐deficiency was shown to exacerbate allergic inflammation and experimental asthma, suggesting a role in the regulation of type II immunity . VISTA −/− mice were also more susceptible to concanavalin A (ConA)‐induced lethality .…”
Section: Vista‐deficiency Enhances Immunitysupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were recently reported in the Fas lpr lupus model where VISTA‐deficiency enhanced disease while VISTA agonists suppressed both cutaneous and systemic lupus . In addition, VISTA‐deficiency was shown to exacerbate allergic inflammation and experimental asthma, suggesting a role in the regulation of type II immunity . VISTA −/− mice were also more susceptible to concanavalin A (ConA)‐induced lethality .…”
Section: Vista‐deficiency Enhances Immunitysupporting
confidence: 83%
“…VISTA is also composed of a single IgV domain and therefore, based on structural insights, we predict that VISTA probably functions primarily as a receptor. This has been corroborated by a number of studies that elucidated the receptor role for VISTA using multiple systems . The second evidence for VISTA function is the ability to impart opposing outcomes of immune responses using agonist and antagonist antibodies.…”
Section: Structurementioning
confidence: 81%
“…Studies by Flies et al have shown that in a murine model of experimental asthma, allergen challenge induced higher levels of Th2 cytokine production and more severe pulmonary inflammation in Vsir −/− mice. 55 THE LIGAND-OR-RECEPTOR PARADIGM BY WHICH VISTA REGULATES T CELL ACTIVATION Due to the lack of knowledge on the cognate receptor for VISTA or associated signaling adaptors, the molecular mechanisms of how VISTA regulates effector T cell activation are not well understood. Despite this limitation, recent studies have demonstrated both cell-extrinsic and intrinsic mechanisms by which VISTA regulates T cell responses.…”
Section: Vista Is a Critical Regulator Of T Cell-mediated Immune Respmentioning
confidence: 99%
“…14 Various studies have investigated that that VISTA regulates Tcell responses in various murine models of carcinoma, autoimmune and allergic disease. 14,[18][19][20][21][22][23] Anti-VISTA treatment exacerbates the development of the T cell-mediated autoimmune disease experimental autoimmune encephalomyelitis in mice. 14 VISTA À/À T cells induce exacerbated graft-versus-host disease compared to wild-type T cells.…”
mentioning
confidence: 99%
“…20 VISTA deficiency or blockade of VISTA also accelerated asthmatic responses. 21,23 Antibodies targeting the immune-checkpoint proteins CTLA-4, PD-1, and PD-L have become new therapies for cancer. [24][25][26][27][28][29] VISTA expression also plays a critical role in shaping anti-tumor immunity.…”
mentioning
confidence: 99%